2009
DOI: 10.1038/nn.2275
|View full text |Cite
|
Sign up to set email alerts
|

Non–cell autonomous influence of MeCP2-deficient glia on neuronal dendritic morphology

Abstract: The neurodevelopmental disorder Rett Syndrome (RTT) is caused by sporadic mutations in the transcriptional factor methyl-CpG binding protein 2 (MeCP2). Although it is thought that the primary cause of RTT is cell autonomous due to lack of functional MeCP2 in neurons, whether non-cell autonomous factors contribute to the disease, is unknown. Here, we show that loss of MeCP2 occurs not only in neurons but also in glial cells of RTT brain. Using an in vitro co-culture system, we find that mutant astrocytes from a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

28
442
6
10

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 423 publications
(486 citation statements)
references
References 52 publications
28
442
6
10
Order By: Relevance
“…In addition, the expression of transgenic MeCP2 in glial cells in the transgenic mice described in this report could contribute to the behavioral amelioration and might explain the different results observed. 23,28 Do our results mean that MeCP2-e1 and MeCP2-e2 are practically interchangeable? Life span, body weight control and anxiety were equally rescued by both isoforms, suggesting equal function at similar levels of expression.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…In addition, the expression of transgenic MeCP2 in glial cells in the transgenic mice described in this report could contribute to the behavioral amelioration and might explain the different results observed. 23,28 Do our results mean that MeCP2-e1 and MeCP2-e2 are practically interchangeable? Life span, body weight control and anxiety were equally rescued by both isoforms, suggesting equal function at similar levels of expression.…”
Section: Discussionmentioning
confidence: 92%
“…Co-staining of transgenic MeCP2 and the intermediate filament marker glial fibrillary acidic protein (GFAP) indicated that none of the transgenic lines express MeCP2 in astrocytes at detectable levels (Supplementary Figure 2a). However, as it has been shown that endogenous MeCP2 expression in glial cells is not easily revealed due to its low levels, 23 we analyzed the expression of the transgenes in primary cultures of mixed cortical cells and found expression of MeCP2 transgenes in some GFAP-positive glial cells in the three transgenic lines studied (Supplementary Figure 2b).…”
Section: Expression Of Isoform-specific Cdnas In Transgenic Micementioning
confidence: 99%
“…A clue stems from the realization that glia and astrocytes contribute to the pathology of both ALS and Rett syndrome (Lioy et al 2011;Phatnani et al 2013;Yasui et al 2013). A common trait shared between ALS and Rett syndrome is a non-cell-autonomous-mediated neuronal death, and glial cells expressing either ALS mutant proteins or reduced levels of MeCP2 secrete a neurotoxin that leads to inhibition of dendritic complexity and neuron death (Ballas et al 2009). Additionally, recent studies have shown that dysregulation of MeCP2 protein, similar to FUS, preferentially affects expression of long genes (Sugino et al 2014;Gabel et al 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Glial-derived lipoproteins containing cholesterol stimulate axon growth 27 and transcription of genes involved in dendrite and synapse development 28 in primary rat retinal ganglion cells; their co-culture with glial cells enhances synaptic activity and neurite outgrowth and branching in Purkinje neurons, 29 and cholesterol deficiency inhibits dendrite outgrowth in primary cortical and hippocampal neurons. 30 Impairments in astrocytic function are increasingly recognized as a culprit in neuronal dysfunction in neurodegenerative diseases, 31 such as amyotrophic lateral sclerosis, 32 Rett's syndrome, 33,34 lysosomal disorders, 35 Alzheimer's disease, 36 and HD. 16 Accordingly, astrocyte kir4.1 ion channel deficits contribute to neuronal dysfunction in Figure 4b is the same.…”
Section: Discussionmentioning
confidence: 99%